Impulsive Perturbations of a Three-Species Food Chain System with the Beddington-DeAngelis Functional Response. (19th January 2012) - Do, Younghae; Baek, Hunki; Kim, Dongseok
Abstract : The dynamics of an impulsively controlled three-species food chain system with the Beddington-DeAngelis functional response are investigated using the Floquet theory and a comparison method. In the system, three species are prey, mid-predator, and top-predator. Under an integrated control strategy in sense of biological and chemical controls, the condition for extinction of the prey and the mid-predator is investigated. In addition, the condition for extinction of only the mid-predator is examined. We provide numerical simulations to substantiate the theoretical results.